Annual banned-substance review: Analytical approaches in human sports drug testing - Thevis, M.; Kuuranne, T.; Geyer, H. (Drug Testing and Analysis, 2019)
A number of high profile revelations concerning anti-doping rule violations over the past 12 months have outlined the importance of tackling prevailing challenges and reducing the limitations of the current anti-doping system. At this time, the necessity to enhance, expand, and improve analytical test methods in response to the substances outlined in the World Anti-Doping Agency (WADA) Prohibited List represents an increasingly crucial task for modern sports drug testing programs. The ability to improve analytical testing methods often relies on the expedient application of novel information regarding superior target analytes for sports drug testing assays, drug elimination profiles, and alternative sample matrices, together with recent advances in instrumental developments. This annual banned-substance review evaluates literature published between October 2017 and September 2018 offering an in-depth evaluation of developments in these arenas and their potential application to substances reported in WADA's 2018 Prohibited List.